Soil stabilisation for DNA metabarcoding of plants and fungi. Implications for sampling at remote locations or via third-parties - Lina A. Clasen (Pensoft Publishers, 2020)
Storage of soil samples prior to metagenomic analysis presents a problem. If field sites are remote or if samples are collected by third parties, transport to analytical laboratories may take several days or even weeks. The bulk of such samples and requirement for later homogenisation precludes the convenient use of a stabilisation buffer, so samples are usually cooled or frozen during transit. There has been limited testing of the most appropriate storage methods for later study of soil organisms by eDNA approaches. Here we tested a range of storage methods on two contrasting soils, comparing these methods to the control of freezing at -80 °C, followed by freeze-drying. To our knowledge, this is the first study to examine the effect of storage conditions on eukaryote DNA in soil, including both viable organisms (fungi) and DNA contained within dying/dead tissues (plants). For fungi, the best storage regimes (closest to the control) were storage at 4 °C (for up to 14 d) or active air-drying at room temperature. The worst treatments involved initial freezing, followed by thawing which led to significant later spoilage. The key spoilage organisms were identified as Metarhizium carneum and Mortierella spp., with a general increase in saprotrophic fungi and reduced abundances of mycorrhizal/biotrophic fungi. Plant data showed a similar pattern, but with greater variability in community structure, especially in the freeze-thaw treatments, probably due to stochastic variation in substrates for fungal decomposition, algal proliferation and some seed germination. In the absence of freeze drying facilities, samples should be shipped refrigerated, but not frozen if there is any risk of thawing.